2003
DOI: 10.1038/sj.npp.1300287
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Dopamine Release in Primates Measured with [11C]Raclopride PET

Abstract: Nicotine-induced dopamine (DA) release constitutes a pharmacological probe of the DA system that has potential use in patients with schizophrenia, who have abnormally elevated DA release after amphetamine administration and possibly abnormalities in nicotinic signaling. We performed positron emission tomography studies in five rhesus monkeys that received i.v. nicotine doses ranging from 0.01 to 0.06 mg/kg. [ 11 C]raclopride was administered with either a bolus plus constant infusion or with paired bolus injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 61 publications
5
44
2
Order By: Relevance
“…Addiction to tobacco is thought to involve the effects of nicotine, its main addictive component (Stolerman et al, 1995), on the dopaminergic system (Balfour et al, 2000;Pidoplichko et al, 1997) as nicotinic receptors have been identified on nigrostriatal and mesolimbic dopaminergic neurons (Clarke and Pert, 1985). Supporting this, studies in rodents and non-human primates show that tobacco or nicotine increase dopamine neuron firing (Grenhoff et al, 1986;Zhang and Sulzer, 2004), increase dopamine release (Dewey et al, 1999;Gallezot et al, 2013;Marenco et al, 2004;Pontieri et al, 1996), and increase dopamine synthesis (Tsukada et al, 2005) in the striatum.…”
Section: Introductionmentioning
confidence: 73%
“…Addiction to tobacco is thought to involve the effects of nicotine, its main addictive component (Stolerman et al, 1995), on the dopaminergic system (Balfour et al, 2000;Pidoplichko et al, 1997) as nicotinic receptors have been identified on nigrostriatal and mesolimbic dopaminergic neurons (Clarke and Pert, 1985). Supporting this, studies in rodents and non-human primates show that tobacco or nicotine increase dopamine neuron firing (Grenhoff et al, 1986;Zhang and Sulzer, 2004), increase dopamine release (Dewey et al, 1999;Gallezot et al, 2013;Marenco et al, 2004;Pontieri et al, 1996), and increase dopamine synthesis (Tsukada et al, 2005) in the striatum.…”
Section: Introductionmentioning
confidence: 73%
“…Striatal DA release in response to a nicotine or cigarette challenge has been demonstrated repeatedly in both non-human primates and humans (Brody et al, 2004a;Dewey et al, 1999;Marenco et al, 2004;Tsukada et al, 2002), with the majority of these studies using PET and the radiotracer 11 C-raclopride (a relatively specific D 2 receptor binder) to demonstrate DA release through radiotracer displacement. These studies have reported a wide range of DA concentration change.…”
Section: Brain Dopamine Responses To Nicotine and Smokingmentioning
confidence: 99%
“…These studies have reported a wide range of DA concentration change. In two studies that examined the question directly (Marenco et al, 2004;Tsukada et al, 2002), nicotine was found to result in less radiotracer displacement than amphetamine, while it has also been reported that nicotine-induced DA release is comparable in magnitude to that induced by other addictive drugs (Pontieri et al, 1996). In addition, an association between 11 C-raclopride displacement and the hedonic effects of smoking (defined as elation and euphoria) has been demonstrated (Barrett et al, 2004), though this study did not find an overall difference between the smoking and non-smoking conditions.…”
Section: Brain Dopamine Responses To Nicotine and Smokingmentioning
confidence: 99%
“…Unlike those psychostimulants, nicotine is known to produce relatively weak elevation in DA levels (Forget et al, 2010;Pontieri et al, 1996), which may explain why initial PET studies in animals report small, inconsistent changes in response to intravenous nicotine (Cumming et al, 2003;Marenco et al, 2004;Tsukada et al, 2002). Subsequently, in some studies smoking nicotine-containing cigarettes produced modest changes in [ 11 C]-raclopride binding in the limbic striatum (Brody et al, 2009;Brody et al, 2006;Brody et al, 2004;Domino et al, 2012;Domino et al, 2013) or in others, changes in [ 11 C]-raclopride binding were limited to those smokers finding the experience of nicotine/smoking pleasurable (Barrett et al, 2004;Montgomery et al, 2007).…”
Section: Introductionmentioning
confidence: 99%